A Study on the History of Mughal Empire: Origins and Expansion of the Mughal Empire (Journal of Advances and Scholarly Researches in Allied Education, 2015)
The Mughal Empire was founded by Babur, a CentralAsian ruler who was descended from the Turko-Mongol conqueror Timur on hisfather's side and from Chagatai, the second son of the Mongol ruler GenghisKhan, on his mother's side. Ousted from his ancestral domains inCentral Asia, Babur turned to India to satisfy his ambitions. He establishedhimself in Kabul andthen pushed steadily southward into India from Afghanistan throughthe Khyber Pass.